Análisis en los procesos logísticos de la reestructuración del área de Logística Internacional en la empresa SERVIENTREGA S.A. (2023)
This paper will describe the different functions that were carried out during the internship in SERVIENTREGA S.A. in the area of international logistics; which included the traceability and control of postal traffic operations and urgent shipments, gathering information from corporate clients, support in the preparation of documents inherent to perform international operations, and other tasks that complemented the knowledge acquired during the learning of this program and finally those that are essential in order to begin the profession of international trade.